Investigasi Miskonsepsi pada Materi Perkembangbiakan Tumbuhan Menggunakan Metode CRI (certainty of response index) di Sekolah Dasar - Darmastuti, Milati; Desstya, Anatri (Cetta: Jurnal Ilmu Pendidikan, 2024)
Science is material that is closely correlated with experiments and observations, as well as the complexity of living things and their lives, including plants. Plant reproduction is considered to be an area of material that is classified as difficult to convey because it is dense and requires long observations. This difficulty then becomes the trigger for misconceptions among students. This research aims to desCRIbe the level of misconceptions among elementary school students regarding plant reproduction material. This type of research is qualitative with a data collection method using a test instrument using the Certainty of Response Index (CRI) method, with a total of 25 questions that have been tested for validity and reliability, with a validity score of 0.468 and a reliability score of 0.60. The validity of this research was checked by testing the validity and reliability of the test instrument, checking the consistency of filling in the CRI values during the research, and using a formula to calculate the incidence of misconceptions. Based on the results of the discussion, it can be concluded that the questions can be declared valid and reliable. The research results showed that 32% had misconceptions, 28% knew the concept with certainty, 29% didn't know the concept correctly, and 4% guessed the answer. The percentage of misconceptions at 32% can be categorized as moderate. The highest misconception in the material explaining perfect flowers was 89%, while the lowest misconception in the material explaining the meaning of vegetative plant reproduction was 0%, which means that no students experienced misconceptions about the material.